User autonomy in implementing additional integrative practices - Ferraz, Ivana Santos (2020)
This study aimed to develop a bioethical reflection on the autonomy of users submitted to Complementary Integrative Practices in the context of the Unified Health System, in the light of the concept of Protection Bioethics. This is an integrative literature review with a time frame from 2007 to 2017, whose search for the material took place in April 2018, at the Virtual Health Library. As a result, it was identified that most of the material analyzed is recent, between 2010 and 2017, written by different professionals who are concerned with studying the topic, in national journals in the Portuguese language, being the predominant interest among pharmacists and nurses. It was possible to perceive that, in the users' conception, the Complementary Integrative Practices investigated positively influence the user's autonomy. Although Complementary Integrative Practices are considered effective strategies in health promotion, challenges arise when integrating them in a context where bioscience dominates in epistemological and cultural aspects. Therefore, it is recommended that research on Complementary Integrative Practice be expanded, and investment in methodologies to raise awareness among the actors involved, aiming at expanding the interface with health promotion, favoring the understanding and consolidation of these practices in the scenario of doing in health.